Smart Greenhouse System On Paprican Plants Based On Internet of Things - Sandi Pamungkas (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2019)
Abstract - Greenhouse method is one of several methods that are very popular to be applied to various types of plants, especially paprika plants. In essence the conditions that must be very guarded in a greenhouse are conditions in the environment such as temperature, air humidity, soil moisture and water pH value. But it is unfortunate that the condition still cannot be monitored properly so that the plants still cannot be maximized. Therefore a smart greenhouse system was created. This smart greenhouse system is a system that later has a function to measure the parameters needed by plants, especially paprika plants such as temperature & humidity, soil moisture, water pH and watering. The purpose of this research is to design a system for monitoring the condition of a plant in a greenhouse, so that later the maintenance for future paprika plants will be more controlled when compared to plants grown outside a greenhouse. In a smart greenhouse system it uses several types of electronic components including DHT-22 sensors, capacitive soil moisture sensors, and pH sensors. The data sent by each sensor will then be sent to thingspeak which we can access anywhere from the smartphone or laptop. For the value of a good temperature for paprika plants is estimated to be 270C to 290C while for the value of good air humidity for paprika plants is in the number 70 relative humidity (RH) to 85 relative humidity (RH) while for the value of soil moisture that is good for paprika plants is in range 70 relative humidity (RH) to 85 relative humidity (RH) and for the pH value of water that is good for paprika plants is in the numbers 6 to 6.5. .Keyword : smart greenhouse, smartphone, DHT-22 sensor, soil moisture sensor, pH sensor, thingspeak, paprika plant.